Dog gets a pet - Mack, Jeff (Ready-to-read graphics. Star reader!, 2024)
"Pony has a surprise for Dog--a pet rock! Dog would have preferred a T-Rex, or a moose, or a cow for a pet, but Pony says if Dog gives the pet rock a name, Dog will like it more. Dog names his pet rock Lulu the T-Rex and says it likes to eat ponies! Uh-oh. Will Dog and Pony and Lulu learn to get along?"--Amazon.com.